Optimisation and biological activities of bioceramic robocast scaffolds provided with an oxygen-releasing coating for bone tissue engineering applications - Touri, Maria; Moztarzadeh, Fathollah; Abu Osman, Noor Azuan; Dehghan, Mohammad Mehdi; Mozafari, Masoud (Elsevier, 2019)
Hypoxia is one of the major challenges after scaffold implantation which can lead to cell necrosis and bacterial infection. Using of supplemental oxygen can increase the cell proliferation, encourage the cell differentiation and prevent the infections. Developing an engineered scaffold with a sustained oxygen release is an outstanding way for addressing the challenges of oxygen deficiency. In this study, the bioceramic scaffolds were fabricated from biphasic calcium phosphate (BCP) powder with the composition of 60% hydroxyapatite (HA) and 40% beta-tricalcium phosphate (β-TCP). The Robocasting technique was utilised for producing a porous structure comprising interpenetrated ceramic rods in a 3-dimensional tetragonal mesh. The scaffold was modelled by the finite element method (FEM) for computing the stress fields and predicting their mechanical performance. Calcium peroxide (CPO), as an oxygen-producing and antimicrobial biomaterial, was mixed with a polycaprolactone (PCL) solution and was coated on the scaffolds by the dip-coating method. The coating layer possessed three different percentages of CPO (1, 3 and 5 wt%). The oxygen-releasing profile proved that this design of coating-scaffold could be effective as a system of oxygen delivery. According to the antibacterial investigations, releasing of CPO from the scaffolds could inhibit the growth of E. coli and S. aureus. SBF tests confirmed that the coated scaffolds because of CPO particles on their surface presented superior apatite precipitation in comparison with the uncoated one. The differentiated osteoblastic function was monitored by measuring the alkaline phosphatase (ALP) activity. The coated BCP scaffolds with 3% and 5% CPO exhibited higher ALP activity compared to the other samples. The results demonstrated that the proposed bioceramic-based scaffolds containing oxygen-generating coating could be optimised to supply an antibacterial performance, ideal mechanical properties, improved ALP activity and higher apatite formation ability. Therefore, these scaffolds can be a promising candidate for applying in bone tissue engineering.